Preto, gordo e cafajeste: a descolonização da imagem negra em Tim Maia - Zonatto, Sidney Rogério Batista dos Santos (2023)
This research project aims to analyze the subjective decolonization of Sebastião Rodrigues Maia, the famous singer Tim Maia. Considering decolonization in the broadest sense of the term and proposing an examination centered on its musical production, lyrics and its aesthetics, but also in interviews, censorship reports and in his biography. The systematization of the wide and complex body of sources between musical and non- musical, as well as the postcolonial theoretical anchoring, allow a more complete panorama of what is proposed as decolonization. Few things have been produced from an academic point of view about Tim Maia, even less about his decolonization, but the investigation of this phenomenon allowed us to glimpse the elaboration of other decolonizations, those of the (sub)urban black youths of Rio de Janeiro who composed and formulated the Black Rio Movement in the 70's. By taking a look at these aspects, the context of this Movement and the echoes of the singer's production on other Afro- diasporic historicities, it is possible to locate aspects of the censorship apparatus in the context of the Brazilian business-military dictatorship, passing through the critique of black essentialism and arriving, for example, in the aesthetic-thematic confluences of rap in the mid-1990s in relation to black music produced in previous decades. With this, we consider important the formulations and studies about the phenomenon of decolonization, mainly to increase the scope and give more visibility to the elaborations of research on other modernities than those centered on the white Eurocentric circuit of the Global North